Pengaruh Pemberian Hidrogen Peroksida (H2O2) Dalam Pengendalian Ektoparasit, Dan Kelangsungan Hidup Benih Ikan Nila Salin (Oreochromis niloticus) Di Balai Besar Perikanan Budidaya Air Payau Jepara - Arini, Priesty Dyah; Muhammad, Fuad; Baskoro, Karyadi; Fahris, Noor (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2018)
Nile tilapia fish (saline) is tolerable to high salinity and has a better resilience in environmental change, make it perfect for fish culture in the ponds. Problems which usually occur in fish culture is disease which is triggered by the decrease of water quality so that the parasytes begin to emerge. The ectoparasyte which usually attacks the fish is Trichodina sp. By adding hydrogen peroxide into the water medium, this type of ectoparasyte is expected to be controlled. This research is conducted to examine the influence of the hydrogen peroxide concentration difference to the increase of water medium quality, ectoparasyte controlling, and the survival rate of nile tilapia fish. The used method is by adding hydrogen peroxide into the water medium in various concentration, 0 ppm as control, 5 ppm, 10 ppm, and 15 ppm given in three times until day 10. The result of this research shown that different hydrogen peroxide concentration may influence the quality of the water medium, controling ectoparasyte,Â increase nile tilapia survival rate. The medium with hydrogen peroxide concentration (15 ppm) shows the best result.Â Keywords: nile tilapia fish, Trichodina sp, hydrogen peroxide, water medium quality, ectoparasyte control, survival rate.